Thoracoscopic‐assisted lung lobectomy in cat cadavers using a resorbable self‐locking ligation device. Issue 4 (15th October 2018) - Nylund, Adam M.; Höglund, Odd V.; Fransson, Boel A.
Abstract: Objective: To compare the maximum pressure sustained by airways sealed with a resorbable ligation device (LigaTie) and with thoracoabdominal (TA) staples during thoracoscopic‐assisted hilar lung lobectomies. Study design: In situ cadaveric study. Animals: Ten feline cadavers. Methods: Twenty lung lobectomies were performed with either a LigaTie or a TA stapler (n = 10 per group) by using a thoracoscopic‐assisted technique. Procedures were randomly performed on the cranial lung lobes only. The distance between the ligation and the hilus was measured on each specimen. Airway pressures were tested to a maximum pressure of 40 cmH2 O. Results: All LigaTie sites reached a maximum airway pressure without leaking and were easily placed at the hilus. Four of 10 TA stapled sites leaked at a mean pressure of 22 cmH2 O ( P  = .010). All leaks occurred when the TA staple line was >5 mm from the hilus; no leaks occurred when the TA staple line was ≤5 mm from the hilus ( P  < .001). No difference was found between fresh and frozen cadavers ( P  = .483) or right vs left lung lobe ( P  = .284). Conclusion: Lung lobectomies were consistently performed at the hilus only when the LigaTie was used. Lung lobectomies were less likely to leak when performed with the LigaTie rather compared with TA staples. Clinical significance: The LigaTie may be an effective alternative for lung lobectomies at the pulmonary hilus in cats and small breed dogs. Our findings provide justification for additional clinical testing.